Numerical derivation of homogenized dynamic masonry material properties with strain rate effects - Wei, X.; Hao, Hong (Pergamon, 2009)
Masonry is a composite material composed of bricks and mortar disposed in a regular arrangement. It is commonly used as load bearing or partition walls in building structures. Owing to limitations of computer power, detailed distinctive modelling of brick and mortar of a realistic masonry structure or a structure with masonry infilled walls is usually not possible. Moreover, no dynamic masonry material model can be found in the open literature. Dynamic masonry material properties are important for an accurate prediction of masonry failure and fragmentation under dynamic loads. In this paper, a continuum damage model with strain rate effect is developed for masonry materials based on the homogenization method. The equivalent elastic properties, strength envelope and dynamic increase factors (DIFs) of strength and moduli for the homogenized masonry material are numerically derived from the simulated responses of a representative volume element (RVE). A numerical model of an RVE is analyzed with detailed distinctive modelling of brick and mortar with their respective dynamic material properties obtained from laboratory tests. The homogenized material model can be used to analyse large-scale masonry structures subjected to dynamic loading.